KONFLIK SOSIAL INTERNAL MASYARAKAT PADA MASA DIBERLAKUKANNYA ATURAN PEMBATASAN SOSIAL DI KOTA PALANGKA RAYA - Yorgen Kaharap; Dotrimensi Dotrimensi (Prodi Sosiologi FISIP UPR, 2022)
In an effort to contain the spread of COVID-19, various states around the world have implemented strict measures to regulate social interactions that have an impact on the interdependence of modern society and Social Conflicts Occur as a result of social restriction policies. The purpose of this paper is to analyze internal household social conflicts. The methodology in this paper uses qualitative. In this article, we argue that the handling of this pandemic has resulted in internal household social conflicts, especially in Palangka Raya which can be interpreted by expanding the formulation of the handoko theory (indicator of internal social conflict). Conflicts are triggered precisely by these indicators. Through this conceptualization, we identify various paradoxes and problems posed by the current pandemic of society and analyze how efforts to overcome them through these indicators. This paper concludes that internal household social conflicts in Palangka Raya that characterize the pandemic, are not phenomena that just pass.